Phenolic composition and antioxidant activity of Eucalyptus grandis, E. urograndis (E. grandis x E. urophylla) and E. maidenii bark extracts - Santos, Sónia A. O.
The phenolic composition of Eucalyptus grandis, Eucalyptus urograndis (E. grandis x E. urophylla) and Eucalyptus maidenii bark is reported for the first time. High performance liquid chromatography-electrospray ionization mass spectrometry (HPLC-ESI-MS) and tandem mass spectrometry (MSn) analysis of the methanol:water (50:50) extracts allowed to identify thirteen, twelve and twenty-four phenolic compounds in E. grand's, E. urograndis and E. maidenii bark extracts, respectively. Furthermore, ellagic acid-rhamnoside, dihydroxy-isopropylchromone-hexoside and dihydroxy-(methylpropyl)isopropylchromone-hexoside are referenced for the first time as constituents of Eucalyptus species. Epicatechin and quercetin-glucuronide are the major phenolic compounds in E. grandis and E. urograndis bark, followed by ellagic acid-rhamnoside and ellagic acid in E. grand's and by galloyl-bis-hexahydroxydiphenoyl (HHDP)-glucose and gallic acid in E. urograndis. Catechin, chlorogenic acid and methyl-ellagic acid-pentose are the major compounds in E. maidenii bark. The phenolic content of the three extracts shows a positive correlation with their antioxidant activities, evaluated by 2,2-diphenyl-2-picrylhydrazyl hydrate (DPPH) radical scavenging, showing activity values between those of two commercial antioxidants, ascorbic acid and butylated hydroxytoluene (BHT). These results, together with the phenolic composition, confirm the high potential of these species as source of biologically active phenolic compounds. (C) 2012 Elsevier B.V. All rights reserved.